Prenatal Exposure to DEHP Induces Neuronal Degeneration and Neurobehavioral Abnormalities in Adult Male Mice. (23rd April 2018) - Barakat, Radwa; Lin, Po-Ching; Park, Chan Jin; Best-Popescu, Catherine; Bakry, Hatem H; Abosalem, Mohamed E; Abdelaleem, Nabila M; Flaws, Jodi A; Ko, CheMyong
Abstract: Phthalates are a family of synthetic chemicals that are used in producing a variety of consumer products. Di-(2-ethylhexyl) phthalate (DEHP) is an widely used phthalate and poses a public health concern. Prenatal exposure to DEHP has been shown to induce premature reproductive senescence in animal studies. In this study, we tested the hypothesis that prenatal exposure to DEHP impairs neurobehavior and recognition memory in her male offspring and we investigated one possible mechanism—oxidative damage in the hippocampus. Pregnant CD-1 female mice were orally administered 200 μg, 500 mg, or 750 mg/kg/day DEHP or vehicle from gestational day 11 until birth. The neurobehavioral impact of the prenatal DEHP exposure was assessed at the ages of 16–22 months. Elevated plus maze and open field tests were used to measure anxiety levels. Y-maze and novel object recognition tests were employed to measure memory function. The oxidative damage in the hippocampus was measured by the levels of oxidative DNA damage and by Spatial light interference microscopic counting of hippocampal neurons. Adult male mice that were prenatally exposed to DEHP exhibited anxious behaviors and impaired spatial and short-term recognition memory. The number of hippocampal pyramidal neurons was significantly decreased in the DEHP mice. Furthermore, DEHP mice expressed remarkably high levels of cyclooxygenase-2, 8-hydroxyguanine, and thymidine glycol in their hippocampal neurons. DEHP mice also had lower circulating testosterone concentrations and displayed a weaker immunoreactivity than the control mice to androgen receptor expression in the brain. This study found that prenatal exposure to DEHP caused elevated anxiety behavior and impaired recognition memory. These behavioral changes may originate from neurodegeneration caused by oxidative damage and inflammation in the hippocampus. Decreased circulating testosterone concentrations and decreased expression of androgen receptor in the brain also may be factors contributing to the impaired neurobehavior in the DEHP mice.